Participating in Christ : explorations in Paul's theology and spirituality - Gorman, Michael J., 1955- (Grand Rapids, MI : Baker Academic, a division of Baker Publishing Group, 2019)
"A world-renowned scholar examines the important Pauline theme of participation in Christ and explores its contemporary significance for Christian life and ministry"--
Participating in Christ : an overview -- The cross : revelation of Christ and God, of humanity and the Church -- Cruciform or resurrectiform? Paul's paradoxical practice of resurrectional cruciformity -- A new translation of Philippians 2:5 and its significance for Paul's theology and spirituality -- The apocalyptic new covenant and the shape of life in the spirit according to Galatians -- Reading Galatians 2:15-21 theologically : beyond old and new, West and East -- New creation! Justification and participation from Galatians to Second Corinthians -- Righteousness, resurrection, reconciliation: from Second Corinthians to Romans -- Theosis in Second Corinthians -- Being "in Christ" today : Paul's letter to the contemporary Church in North America -- Paul on practicing and preaching the resurrection today.
Includes bibliographical references and index.
Keywords: Jesus Christ -- Person and offices; Bible. -- Theology; Bible. -- Criticism, interpretation, etc